2022
DOI: 10.3389/fnut.2022.1065543
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed electric field increases the extraction yield of extra virgin olive oil without loss of its biological properties

Abstract: IntroductionPulsed electric field (PEF) has been used for improving extraction of extra virgin olive oil (EVOO). However, the biological changes induced by the consumption of pulsed electric field-obtained extra virgin olive oil (PEFEVOO) have not been studied yet.Materials and methodsEVOO oils from Empeltre variety were prepared by standard (STD) cold pressure method involving crushing of the olives, malaxation and decanting and by this procedure including an additional step of PEF treatment. Chemical analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…It has been noted that the enhanced extraction capability of this process justifies the energy requirements, making Pulsed Electric Field (PEF) technology a promising method for extracting oil from the olive paste matrix, with positive effects on the quality of the final products. Moreover, a slightly higher Yield of oil from untreated and PEF-treated olive paste malaxed at different temperature [25].…”
Section: Quality Of Pef-extracted Olive Oilmentioning
confidence: 98%
See 2 more Smart Citations
“…It has been noted that the enhanced extraction capability of this process justifies the energy requirements, making Pulsed Electric Field (PEF) technology a promising method for extracting oil from the olive paste matrix, with positive effects on the quality of the final products. Moreover, a slightly higher Yield of oil from untreated and PEF-treated olive paste malaxed at different temperature [25].…”
Section: Quality Of Pef-extracted Olive Oilmentioning
confidence: 98%
“…At this time, an extra yield of 1.9 ± 0.3% was obtained for PEF samples compared to the untreated one. However, when a longer time of malaxation was used, these yield differences were reduced [25]. Yield of oil from PEF-treated and untreated olive paste.…”
Section: Evoo Oil Yield Increasementioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the temperature should be monitored and controlled to minimize the degradation of the thermolabile compounds in the plant cells [113]. For this purpose, mild treatments or circulating cooling water would aid in minimizing the associated temperature increase in the system, which would also help to preserve the quality attributes of the tested food [167,229,230].…”
Section: Existing Challenges For Pef Systemsmentioning
confidence: 99%
“…Antonia Tamborrino et al reported that, under energy-specific input of 5.1 kg/kJ, PEF treatment significantly enhances extractability of olive paste without adverse effects on legal quality and sensorial properties [23]. Martínez-Beamonte et al [24] utilized PEF technology for the processing of extra virgin olive oil (EVOO), and their research revealed that PEF application resulted in a 17% increase in oil yield, while maintaining the chemical composition of plant sterols, phenolic compounds, and microRNAs largely unchanged. Only female mice fed with PEF-treated EVOO exhibited a decrease in total plasma cholesterol levels; however, no significant alterations were observed in terms of atherosclerosis or liver fat degeneration, further supporting the safe utilization of PEF-treated EVOO as food.…”
Section: Introductionmentioning
confidence: 99%